Private Equity and Buyouts (MBO and LBO): Analysis of Certain Structures under Peruvian Corporate and Tax Law - Hernández Gazzo, Juan Luis (2007)
This paper analyzes private equity transactions, which have become the leading force in the world economy, combining management buyouts (MBO) and leveraged buyouts (LBO) from a corporate and tax legal point of view. The authors begin with an approach to the basic concepts of these operations and how they have developed and influenced the Peruvian legal system. To that extent, they examine three corporate structures or modalities for the acquisition of the Target Company that can be used to carry out such transactions: (i) MBO/LBO through Newco, (ii) MBO/LBO through Newco and a subsequent merger by absorption between Newco and the Target Company, and (iii) MBO/LBO in the Target Company under a recapitalization structure (RECAP). In turn, some challenges that arise in the practice of these operations in the Peruvian context are identified, such as the legal limitation of indebtedness, stock market regulation, creditor protection, among others.